Cytomorphological and immunocytochemical evaluation of fine needle aspirates from high grade non-Hodgkin's lymphomas. - Schmitt, F. C. [UNESP]; Maeda, S. A. [UNESP]; Hokama, N. K. [UNESP]; Machado, P. E. [UNESP]; Niero-Melo, L. [UNESP] (My University, 1992)
1. Fine needle aspirates from ten patients with high-grade malignant non-Hodgkin's lymphomas were analyzed by cytomorphology and immunocytochemistry. 2. The following morphologic diagnoses were made: lymphoblastic lymphoma (3 cases), Burkitt's lymphoma (3 cases), mixed small and large cell lymphomas with predominance of large cells (2 cases), and centroblastic lymphoma (2 cases). Immunocytochemistry showed a B-cell phenotype in five cases and a T-cell phenotype in four. One case of lymphoblastic lymphoma was negative for the T and B cell markers used. 3. The results of histological and immunohistochemical analyses performed on surgical biopsies from 8 patients confirmed the morphological diagnosis in all cases. Two cases of Burkitt's lymphoma were submitted only to cytological and immunological diagnosis. 4. The high diagnostic accuracy of combined cytomorphology and immunocytochemical assessment of fine needle aspirate samples validates the use of the technique in the diagnostic work-up of high-grade non-Hodgkin's lymphomas.